Get Smart - Caan, James; 1968-; Koechner, David; Murray, Bill; Crews, Terry; 1962-; 1950 September 21-; Warburton, Patrick; Oka, Masi.; Torrence, Nate; 1977-; Brooks, Mel; et al. (Burbank, CA, 2008)
Agent 86 is the bungling secret agent Maxwell Smart. He works for CONTROL. They are on a mission to battle the forces of their evil crime nemesis known as KAOS. Smart has along side with him the competent and beautiful Agent 99. The headquarters of the U.S. spy agency CONTROL is attacked and the identities of its agents are compromised, the Chief has no choice but to promote his analyst Maxwell Smart, who has dreamed of working in the field with superstar Agent 23. Smart will do whatever it takes to thwart the latest plot for world domination by KAOS.
Keywords: Drama; United States; United States; Drama; Man-woman relationships; Implements, utensils, etc; Drama; United States; Agents provocateurs; Espionage; United States; Drama; Feature films; Video recordings for the hearing impaired; Drama; Thrillers (Motion pictures); Action and adventure films; Comedy films